Student engagement in reader's theater : underlying factors and effects on learning and group management - Sillgren, Miila; Hietala, Sari (2022)
This study examined the underlying factors of student engagement, as well as the effects of student engagement on expressive reading and teacher-experienced group management in the context of the reader’s theater program. The participants were 99 randomly selected dysfluent readers, who participated in an eight-week reader’s theater program. Students were divided into small-groups of five students (N = 20), half of whom had a clear goal for their training (i.e., preparing a play for their classmates) and half did not. Expressive reading was measured before and after the intervention. Student engagement and teacher-evaluated group management were measured after the intervention. The data was analyzed using multilevel regression analyses. The results indicated that student engagement had a positive effect on both the group management and the improvement in expressive reading during the intervention. Girls showed higher engagement than boys. In addition, reading-related enjoyment and the goal to perform enhanced student engagement.